Features of Islamic websites, perceptions of Muslim users and utilization behavior: a conceptual model - Aliyu, Mansur; Tambawal, Abubakar B.; Mahmud, Murni; Nasser, Rasheed M. (Umaru Ali Shinkafi Polytechnic Sokoto, Nigeria, 2016)
Islamic websites demand special attention due the nature of the content delivered to the users. To deliver satisfying online knowledge and practice for Muslim Ummah, it is important to identify and evaluate the overall features of Islamic website (Iweb). In this paper, we explore the literature on Islamic website and e-consumer and developed a conceptual model that identifies perceived Muslim user satisfaction. The paper examines three issues namely; features of Iweb user satisfaction, perceived dimensions of this satisfaction judgment, and consequence of Muslim user satisfaction with Iweb.